Mechanical Tunability via Hydrogen Bonding in Metal-Organic Frameworks with the Perovskite Architecture. - Wei Li; Thirumurugan, A.; Barton, Phillip T.; Zheshuai Lin; Henke, Sebastian; Yeung, Hamish H.-M.; Wharmby, Michael T.; Bithell, Erica G.; Howard, Christopher J.; Cheetham, Anthony K. (Journal of the American Chemical Society, 2014)
Two analogous metal-organic frameworks (MOFs) with the perovskite architecture, [C(NH)][Mn-(HCOO)] (1) and [(CH)NH][Mn(HCOO)] (2), exhibit significantly different mechanical properties. The marked difference is attributed to their distinct modes of hydrogen bonding between the A-site amine cation and the anionic framework. The stronger cross-linking hydrogen bonding in 1 gives rise to Young's moduli and hardnesses that are up to twice those in 2, while the thermal expansion is substantially smaller. This study presents clear evidence that the mechanical properties of MOF materials can be substantially tuned via hydrogen-bonding interactions.